Personal, familial and socio-economical characteristics of children under five years old, with acute respiratory infection in Tabriz Iran - Valizade Soosan (Iran University of Medical Sciences, 1994)
This is a descriptive field study. The aim of this study was to find Personal, familial and socio-economical characteristics of children under five years old, and relationships between these characteristics with acute respiratory infection. The Sample was 60 children with acute respiratory infection. Data gathered by a questionair include 44 question about Personal, familial and socio-economical characteristics of children. Results: most of children were boys less than one year old. Most of them had malnutrition and did not complete their vaccination program. Most fathers of the children were smokers and most of parents were low literacy.